The role of magnetic resonance imaging in the evaluation of scaphoid fractures - Wong, Steven B. S. (J Med Radiat Sci, 2019)
Radiographs are currently accepted as the first‐line modality for the investigation of scaphoid fractures. Early use of magnetic resonance imaging (MRI) in patients with radio‐occult scaphoid fractures has been shown to be beneficial in the management of such patients. Incorporation of early MRI into the management protocol for scaphoid fracture is recommended. [Image: see text]